ANALISIS DETERMINAN PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DI PROVINSI BANTEN - Wieta Chairunesia (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
This study was conducted to see the effect of Personal Tax Payers, the BI Rate, Inflasidan the GDP of the Income Tax Receipts private in Banten province. This study used multiple linear regression analysis. The results of this study indicate that the amount of the individual taxpayer affected positively and negatively affect the GDP of the Personal Income Tax Revenue. Meanwhile, two other variables in this study, the BI Rate and Inflation does not affect the Personal Income Tax Revenue. This study uses a quantitative approach and using secondary data obtained from the Regional Office of Directorate General of Tax Banten, Bank Indonesia, and the body of the Central Statistics Banten Province. Data used in the form of quarterly data, starting from the first quarter of 2007 until the third quarter of 2014.